Exponents of Emotions in Father’s Blogs [a Contribution to Linguistic and Cultural Research on the Modern Image of a Man] - Suska, Dorota (Poznańskie Studia Slawistyczne, 2015)
The aim of the presented analysis is to show the exponents of excitement in the online genre – father’s blogs. Men’s parenting blogs reflect changes in the field of parenting, where father begins to appear – as an active and participating. This role goes beyond the stereotype of the male and the previous experience of fathers – both media and private. Therefore, the paternal narrative in blogs is for linguists valuable research material, that shows, among others, different aspects of male emotionality and ways to verbalize it. The emotional component of father`s image is created by means expressing feelings (not naming them), polyfunctional, used in unusual combinations and contexts.